Study on Human Resource Barrier on the Path of Economic Development (Orienting to Socialism) in Hochiminh City, Vietnam - Hanh, Vu Thi Kim (Modern Perspectives in Economics, Business and Management Vol. 7, 2021)
The paper analyzes and evaluates the human resource barrier of Hochiminh city, Vietnam (HCM VN), Vietnam is on the path of economic development orienting to socialism. Author uses quantitative methods with multivariate regression (MR) to assess the human resource situation of HCM VN. Based on the analysis results, the author will recomend policy implications to overcome this barrier. The study objectives are to analyse the impact of human resource on path of economic development orienting to socialism, the case of HCM VN, based on study results the author then have suggestion to have improvement the situation of human resource barrier. The highlight findings are total number of female employees, total number of employees who have been career trained, total number of employees who have been graduated high school and the labor index that all impact on GDP in HCM VN. So, in ordere to improve the GDP in HCM VN we can improve these four variables by increasing the number of female employees, focusing on training employees, maximizing the number of high school graducation of employees and improve the labor index.